Extracellular Vesicle Characteristics in β-thalassemia as Potential Biomarkers for Spleen Functional Status and Ineffective Erythropoiesis - Levin, Carina; Koren, Ariel; Rebibo-Sabbah, Annie; Koifman, Naama; Brenner, Benjamin; Aharon, Anat (Frontiers in Physiology, 2018)
-Thalassemia major (β-TM) is a therapeutically challenging chronic disease in which ineffective erythropoiesis is a main pathophysiological factor. Extracellular vesicles (EVs) are membrane-enclosed vesicles released by cells into biological fluids; they are involved in intercellular communication and in multiple physiological and pathological processes. The chaperone heat-shock protein 70 (HSP70), which is released from cells via EVs, aggravates ineffective erythropoiesis in β-TM. We propose that β-TM EVs show specific signatures, reflecting disease mechanisms, stages and severity. Our study aims were to define EV profiles in β-TM patients, investigate the influence of hypersplenism and splenectomy on EV features, and explore the association of circulating EVs with ineffective erythropoiesis and iron-overload parameters. We characterized circulating EVs in 35 transfusion-dependent β-thalassemia patients and 35 controls using several techniques. Nanoparticle-tracking analysis revealed increased EV concentration in patients vs. controls (P = 0.0036), with smaller EV counts and sizes in patients with hypersplenism. Flow cytometry analysis showed lower levels of RBC and monocyte EVs in patients vs. controls. RBC-EV levels correlated with patient hematocrit, reflecting degree of anemia. The procoagulant potential of the EVs evaluated by flow cytometry revealed lower levels of endothelial protein C receptor-labeled EVs in patients vs. controls, and increased tissue factor-to-tissue factor pathway inhibitor-labeled EV ratio in splenectomized patients, suggesting a hypercoagulable state. Protein content, evaluated in EV pellets, showed increased levels of HSP70 in patients (P = 0.0018), inversely correlated with transfusion requirement and hemoglobin levels, and positively correlated with reticulocyte, erythropoietin and lactate dehydrogenase levels. This first description of EVs in patients with hypersplenism reveals the spleen's importance in EV physiology and clearance. Circulating EV-HSP70 levels were associated with markers of ineffective erythropoiesis, hemolysis and hematological disease severity. EV analysis in β-TM—reflecting spleen status, hypercoagulability state and ineffective erythropoiesis—may serve as a biomarker of disease dynamics, supporting both anticipation of the risk of complications and optimizing treatment.